ON THE VERGE OF COLLAPSE. FRUSTRATION EXPERIENCES WITH NETWORKED MEDIA AND THE ROLE OF SOCIAL SUPPORT - Peil, Corinna (AoIR Selected Papers of Internet Research, 2021)
This proposal investigates experiences of frustration with networked media from a users’ perspective. It explores how these experiences are resolved and what role helping friends and family members play in this process. Experiences of frustrations refer to concrete problems in the use of networked media. The examination of their causes and elimination helps to better understand the socio-technical logics of commercial media technologies as well as their impact on everyday life. This study seeks to offer insights into societal power relations with regard to succeeding in and shaping the ongoing digital transformation process. It thus contributes to the wider field of digital inequalities research. Theoretically, my considerations are guided by the concept of media deconvergence which highlights the disorder and messiness of converging media environments. Furthermore, I am inspired by the domestication approach and by “broken world thinking" (Jackson 2014), which takes disruptions and failures as a starting point for analyzing socio-technical change. Insights into novel forms of expertise and changing constellations of support and neediness were gained on the basis of a qualitative study consisting of visualizations of support networks and their written reflection and explanation as well as guided interviews about expertise and mutual support in media usage.